Pengaruh Internet Terhadap Kemudahan Mengakses Konten Porno Di SMP Negeri 35 Palembang - Putra, Deovan Kresnanda; Fauzi, Taty; Putri, Ramtia Darma (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
This study examines the influence of ease of accessing the internet which aims to determine whether there is an influence on watching pornographic content and its impact on sexual harassment at SMP Negeri 35 Palembang. The approach used is a quantitative survey. From data processing, it was obtained that the average value of the questionnaire variable X was 40.20 and the average value of the questionnaire variable Y was 40.87. Based on the normality test it was stated that the sample came from a normal population. Based on the linearity test it was stated that the sample came from a linear population, then based on the hypothesis test it was known that the fcount was 13.166 with a significance value of 0.001 <0.05. Thus Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the results of the analysis and discussion of the questionnaire data, it can be concluded that there is an influence from the ease of accessing the internet on pornographic content and its impact on sexual harassment.